The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/molecules26195770
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Biological Evaluation and In Silico Study of Benzyloxybenzaldehyde Derivatives as Selective ALDH1A3 Inhibitors

Abstract: Aldehyde dehydrogenase 1A3 (ALDH1A3) has recently gained attention from researchers in the cancer field. Several studies have reported ALDH1A3 overexpression in different cancer types, which has been found to correlate with poor treatment recovery. Therefore, finding selective inhibitors against ALDH1A3 could result in new treatment options for cancer treatment. In this study, ALDH1A3-selective candidates were designed based on the physiological substrate resemblance, synthesized and investigated for ALDH1A1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 52 publications
(59 reference statements)
2
29
0
Order By: Relevance
“…The similarity in the values for IC 50 and K D furthermore suggested that this inhibitory activity was caused by the binding affinity we had observed. Given that selective inhibitors of ALDH1A3 have been successively reported (Gelardi et al, 2021;Ibrahim et al, 2021;Jiménez et al, 2019), the potency and selectivity of the compound we have discovered will have some significance, and the precise SAR analyses will be reported elsewhere.…”
Section: Discovery Of Aldh1a3 As the Protein Binding To A Selected Ch...mentioning
confidence: 96%
“…The similarity in the values for IC 50 and K D furthermore suggested that this inhibitory activity was caused by the binding affinity we had observed. Given that selective inhibitors of ALDH1A3 have been successively reported (Gelardi et al, 2021;Ibrahim et al, 2021;Jiménez et al, 2019), the potency and selectivity of the compound we have discovered will have some significance, and the precise SAR analyses will be reported elsewhere.…”
Section: Discovery Of Aldh1a3 As the Protein Binding To A Selected Ch...mentioning
confidence: 96%
“…ALDH1A1, ALDH1A3, ALDH2 and ALDH3A1 have structural and functional differences in substrate binding site, cofactor dissociation, enzyme kinetics, and ratelimiting steps, which facilitates the design of selective inhibitors and enzymatic activity tracers; in particular, ALDH1A1 substrate binding pocket has a wider access tunnel than ALDH2 or ALDH3A1, allowing ALDH1A1 to accommodate larger and more rigid ligands than other ALDH isoforms [138,139].…”
Section: Inhibition Of Aldh As a Potential Therapeutic Approachmentioning
confidence: 99%
“…Recently, our group has discovered a number of compounds with ALDH-affinic properties ( Figure 1 ), compounds 1 – 6 , 15 – 19 , 23 – 28 , and 32 – 34 , which have been investigated on several ALDH-expressing cancer cell lines and have shown promising cytotoxic results [ 21 , 22 ]. These compounds have been found to work via a variety of mechanisms, ranging from inhibiting to activating particular ALDH isoforms [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group has discovered a number of compounds with ALDH-affinic properties ( Figure 1 ), compounds 1 – 6 , 15 – 19 , 23 – 28 , and 32 – 34 , which have been investigated on several ALDH-expressing cancer cell lines and have shown promising cytotoxic results [ 21 , 22 ]. These compounds have been found to work via a variety of mechanisms, ranging from inhibiting to activating particular ALDH isoforms [ 21 , 22 ]. In particular, compound 15 was the most potent ALDH1A3 inhibitor, followed by compounds 16 , 18 , and 1, with remaining enzyme activities of 0.14%, 4.27%, 16.01%, and 21.07%, respectively, compared to the control enzyme activity [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation